SULFUR ABUNDANCE IN THE GALACTIC DISC STARS - Paramonova, O. P.; Mishenina, T. V.; Chepizhko, O. (Одеські астрономічні публікації, 2013)
The  sulfur abundance was determined by the synthetic spectrum method in the stars with metallicity close to that of the Sun. The comparison with the results of other authors, as well as the nucleosynthesis  computations were made.